RNA interference-mediated knockdown of genes involved in sugar transport and metabolism disrupts psyllid Bactericera cockerelli (Order: Hemiptera) gut physiology and results in high mortality - Arad, Neda; Paredes-Montero, Jorge R.; Mondal, Mosharrof Hossain; Ponvert, Nathaniel; Brown, Judith K. (Frontiers in Insect Science, 2023)
The causal agent of zebra chip of potato and vein-greening diseases of tomato is "Candidatus Liberibacter solanacearum" (CLso), a fastidious bacterium transmitted by the potato psyllid. In the absence of disease-resistant cultivars, disease management has relied on minimizing vector population size to reduce CLso transmission, which requires frequent insecticide applications. There is growing interest in the use of RNA interference (RNAi) technology to supplant traditional insecticides with biopesticides. This requires knowledge of genes essential for insect livelihood whose knockdown leads to significant mortality or other phenotypes. Such candidate genes can be evaluated by reverse genetics approaches to further corroborate predicted gene function. Here, five potato psyllid genes involved in sugar homeostasis in the potato psyllid gut, α-glucosidase1 (AGLU1), aquaporin2 (AQP2), facilitated trehalose transporter1 (TRET1), Trehalase1 (TRE1), and Trehalase2 (TRE2), were investigated as candidates for effective gene silencing. Potato psyllid dsRNAs were designed to optimize knockdown of gene targets. Third instar PoP nymphs were given a 48-hr ingestion-access period (IAP) on individual or groups of dsRNA in 20% sucrose. Mortality was recorded 0, 3, 5, 7, and 9 days post-IAP. Gene knockdown was analyzed on 9-d, post-IAP by quantitative real-time reverse-transcriptase polymerase chain reaction amplification. The individual or stacked dsRNA combinations resulted in 20-60% and 20-40% knockdown, respectively, while subsequent psyllid mortality ranged from 20-40% to >60% for single and stacked dsRNA combinations, respectively. Reverse genetics analysis showed that simultaneous knockdown of the five selected candidate genes with predicted functions in pathways involved in sugar-homeostasis,metabolism, and -transport yielded the highest mortality, when compared with single or combinations of targets. Results confirmed the functions afforded by psyllid gut genes responsible for osmotic homeostasis and sugar metabolism/transport are essential for livelihood, identifying them as potentially lucrative RNAi biopesticide targets and highlighted the translational relevance of targeting multiple nodes in a physiological pathway simultaneously.